2020
DOI: 10.1088/1402-4896/ab9ed3
|View full text |Cite
|
Sign up to set email alerts
|

Total branching ratio of the K two-nucleon absorption in 12C

Abstract: This work is a critical re-analysis of the results obtained by the AMADEUS collaboration, concerning the measurement of the K− multi-nucleon absorption reactions, on a 12C target, in the Λp final state (Del Grande et al 2019 Eur. Phys. J. C 79, 190). We show that a good estimate of the K− two-nucleon absorption total branching ratio can be extracted, given that the measured final state interactions and conversion reactions contain information on almost all the remaining hyperon-nucleon final state combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…+5 −6 (syst.)) % aligns with the K − multi-nucleon absorption BRs measured in bubble chamber experiments [49,50]. Combining the experimental BRs for processes leading to Λp pair production (16.1 ± 2.9(stat.)…”
Section: Experimental Facilitysupporting
confidence: 78%
“…+5 −6 (syst.)) % aligns with the K − multi-nucleon absorption BRs measured in bubble chamber experiments [49,50]. Combining the experimental BRs for processes leading to Λp pair production (16.1 ± 2.9(stat.)…”
Section: Experimental Facilitysupporting
confidence: 78%
“…In Ref. [45] it is demonstrated that the sum of the K − 2NA BRs measured in Ref. [34] (also reported in Fig.…”
Section: K − Multi-nucleon Absorption Branching Ratios and Cross Sectionsmentioning
confidence: 82%
“…2 top panel) gives an estimate of the total BR of the K − 2NA process in 12 C. This is motivated by the fact that almost all the hyperon-nucleon combinations emerging as primary products of the K − 2NA process contribute to the FSI and / conversion reactions in the measured p final state (see Ref. [45] for the details). The sum of the K − 2NA BRs measured in Ref.…”
Section: K − Multi-nucleon Absorption Branching Ratios and Cross Sectionsmentioning
confidence: 99%
“…Finally, we add a contribution to a non-mesic capture which contributes only to absorptive potential, denoted by NN. An experimental finding [31] is that it contributes 12% of all captures in Helium (see also [32]). The non-mesic interaction is expected to contribute a negligible shift, typical of large final phase space.…”
Section: Modelmentioning
confidence: 99%